Tax depreciation and the need for the reserve ratio test - Pollock, Richard Leo. (Washington, Dept. of the Treasury; [for sale by the Supt. of Docs., U.S. Govt. Print. Off., 1968)
The work addresses some basic issues related to the persistent problem of depreciation for tax purposes, particularly "is it desirable as a matter of tax policy to enforce conformity between tax and actual life? and "is the reserve ratio test an efficient means of enforcing this conformity?
Bibliography: p. 119-120.
osc 11/03/2019
Loans
Keywords: Depreciation allowances